2012
DOI: 10.4137/jcnsd.s6692
|View full text |Cite
|
Sign up to set email alerts
|

New and Emerging Disease-Modifying Therapies for Relapsing-Remitting Multiple Sclerosis: What is New and What is to Come

Abstract: The therapeutic landscape for multiple sclerosis (MS) is rapidly changing. Currently, there are eight FDA approved disease modifying therapies for MS including: IFN-β-1a (Avonex, Rebif), IFN-β-1b (Betaseron, Extavia), glatiramer acetate (Copaxone), mitoxantrone (Novantrone), natalizumab (Tysabri), and fingolimod (Gilenya). This review will highlight the experience to date and key clinical trials of the newest FDA approved agents, natalizumab and fingolimod. It will also review available efficacy and safety dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…These data also suggest that MMF may be effective for treating other hyperproliferative skin disorders. In addition, a drug containing DMF as its major ingredient, Tecfidera or BG-12 (Ruggieri et al, 2014) is currently available on the US market for the treatment of multiple sclerosis (Nicholas et al, 2012;Salmen and Gold, 2014). Thus, our results suggest the possibility of repurposing this already US Food and Drug Administration-approved drug for the benefit of psoriatic patients.…”
Section: Mmf-induced Effects In Keratinocytesmentioning
confidence: 80%
“…These data also suggest that MMF may be effective for treating other hyperproliferative skin disorders. In addition, a drug containing DMF as its major ingredient, Tecfidera or BG-12 (Ruggieri et al, 2014) is currently available on the US market for the treatment of multiple sclerosis (Nicholas et al, 2012;Salmen and Gold, 2014). Thus, our results suggest the possibility of repurposing this already US Food and Drug Administration-approved drug for the benefit of psoriatic patients.…”
Section: Mmf-induced Effects In Keratinocytesmentioning
confidence: 80%
“…This review revealed there were some side effects from administering fingolimod, such as bradycardia, first or second heart block, macular edema, increased serum alanine aminotransferase (ALT), lymphopenia, and infection. Most of those side effects were infrequent and resolved with discontinuation of fingolimod (Nicholas et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Данные результаты послужили основанием для регистрации препарата алемтузумаб для лечения взрослых пациентов с РРС с активным по клиническим и нейровизуализационным параметрам. В настоящее время место алемтузумаба в терапевтическом алгоритме РС определяется поразному [16][17][18]. Согласно рекомендациям ЕМА препарат показан для лечения взрослых пациентов с РРС с признаками активности заболевания, определяемыми на основании клинической картины и данных нейровизуализационных исследований.…”
Section: клиническая эффективностьunclassified